Tantangan Dalam Mengembangkan Karakter Gembala Sidang di Gereja Kemah Injil Indonesia Koordinator Alor Selatan: Analisis dan Solusi - Tansi, Filmon; Taopan, Serly Sariana; Natoni, Priskha; Rouw, Julian Frank (Teokristi: Jurnal Teologi Kontekstual dan Pelayanan Kristiani, 2025)
The Indonesian Gospel Tabernacle Church, South Alor Coordinator, is one of the seven coordinators under the auspices of the GKII Alor Region. It should have paid special attention to church issues, including talking about the character of a pastor as a leader in carrying out pastoral services. Based on the findings that occurred, the efforts of the pastors in the South Alor Coordinator in realizing the character of a pastor who has the character of Christ, always get challenges both internally (within themselves) and externally (outside) so that the services carried out cannot run optimally and correctly. The pastors in the sense of the related spiritual leaders should have paid special attention to the causes of the obstacles to character formation for a pastor, so that the services carried out can run according to the will of the Triune God. Therefore, the hope of this study is to be able to provide an explanation of the challenges in developing the character of a pastor in the South Alor Coordinator, as well as to be able to provide solutions. The method used in this study is a qualitative research method, with a pattern of conducting observations, interviews and literature. The researcher used this research because he wanted to know in full what the challenges were in developing the character of the pastor in the scope of the Alor Selatan Coordinator’s ministry and at the same time provide the right solution so that the ministry carried out can glorify the Triune God. Keywords: GKII Alor Selatan Coordinator, Pastor, Ministry.